KONSTRUKSI HARMONISASI MELALUI MODEL PEMBELAJARAN IBK BERBASIS PENDIDIKAN MULTIKULTURAL - Ulmi, Tiara Fahmiyatul; Maftuh, Bunyamin; Wilodati, Wilodati (Universitas Tanjungpura, 2022)
The diversity that exists in Indonesia is a problem such as conflict, violent discrimination both in the community and in education. Building a harmony in diversity requires the cultivation of values that uphold equality, respect differences, anti-discrimination and so on. One of them is through multicultural education which is integrated in subjects such as sociology subjects. In order for the learning objectives to be achieved, it is necessary to use an appropriate learning model to instill multicultural values. The purpose of this paper is to provide new ideas about the harmonization construct through the IBK (Group Learning Interaction) learning model based on multicultural education. The method used in this paper is the literature review method. The result of this writing is that the instilling of multicultural values in schools is integrated in every subject. One of them is sociology subjects through the IBK learning model, where teachers from planning, implementing to evaluation will be adjusted to multicultural values.The conclusion of this paper is that the harmonization construction using the multicultural-based IBK (Group Learning Interaction) model is expected to be able to instill multicultural values so that harmony will be built, and harmony in diversity starting from the school environment whose output will have an impact on the wider community. This IBK learning model emphasizes interaction activities in a study group which consists of various individuals from different backgrounds in order to complete learning tasks together through critical discussion to solve problems and find solutions by upholding the values of democracy, humanism, nationalism, equality and tolerance. Therefore, educators need to do it through the process of planning, implementing and evaluating learning.